(untitled) (International Journal of Engineering and Computer Science, 2017)
The basic idea of the Visual Cryptography is to encrypt a secret image into n number of meaningless share images. The Visual Cryptography technique cannot leak the encrypted information of the shared secret by virtue of any combination of the n share images combined together. The share images are printed on transparencies and distributed as shares such that, when the shares are superimposed, a concealed secret image is discovered. The human visual system can recognize the shared secret image without using any computational devices. It needs neither cryptography knowledge nor complex computation. The Visual Cryptography technique for multiple secrets is proposed, which encrypts more than one secret into the equivalent number of share images .The traditional visual secret sharing scheme uses a pre-defined pattern book to generate shares, which leads to a pixel expansion on share images. Thus to minimize the pixel expansion problem in VC scheme a new system is invented which can share two binary secret images on two rectangular share images without pixel expansion. The proposed approach, not only has good contrast, but also has an excellent recovery quality for secret image and the critical problem of pixel expansion is minimized.